simplify the question
![simplify the question class=](https://us-static.z-dn.net/files/db8/d2eb9aab6436a832b475dfaafa2d2b43.png)
Answer:
-4x²+5x+3
Step-by-step explanation:
Actually, the question itself is the simplified version. I just rearranged it by looking at the variable and the exponents.
Hope it helps!
Answer:
Given 5x-4x²+3
so as here it is in the form of ax²+bx+c
so we have to simply make it an quadratic equation
so -4x²+5x+3 =0
so then x = -5± √5²-4(-4)×3/2(-4)
so x =√73 + 5/8 after simplification
so 5x+3 = -4x²(x-(5-√73)/8)(x-(√73+5)/8)
Hope it helps